2022-RA-1621-ESGO Role of PET-CT and CeCT in calculating preoperative PCI in patients with epithelial ovarian cancer. (20th October 2022) - Martinez, Monica Gutierrez; Boria, Felix; Sancho, Lidia; Alcazar, Andrés; Chiva, Luis; Vázquez, Daniel; Castellanos, Teresa
Abstract : Introduction/Background: The objectives are to compare the efficacy between preoperative PET/CT and CeCT findings according with the surgical findings in patients that underwent surgery for epithelial ovarian cancer treatment and to evaluate the correlation between preoperative PCI calculated in both PET/CT an CeCT with surgery. Methodology: Retrospective unicentric observational study reviewing data of 30 patients diagnosed with epithelial ovarian cancer (primary or recurrence) and operated between July 2018-February 2021 in Clinica Universidad de Navarra. Every patient underwent PET/CT and CeCT. PET/CT was independently evaluated by a nuclear medicine doctor (PET-CT) and CeCT by an expert radiologist in gynecologic malignancies.PCI in surgery was calculated by two different gynecologic oncologists. If there was any discordance between them, a media between both scores was applied.Medical history and demographic data, preoperative FIGO stage, PET/CT findings, CT findings final pathology diagnosis, type of surgery and perioperative details were reviewed. Intraclass correlation coefficient was calculated to compare the PCI obtained preoperatively in PET/CT and CeCT to the PCI obtained in the final surgery. Results: The interclass correlation coefficient in the global cohort of patients compared to the PCI calculated intraoperatively was 0.867 for CeCT and 0.807 for PET-CT.Regarding the prediction of complete cytoreduction, the area under the curve in the CeCT was 0.659 and 0.690 in the PET-CT. Conclusion: Despite the small sample size, this initial study highlights that CeCT is more effective in calculating PCI preoperatively, however, PET-CT is better at predicting complete cytoreduction. Further validation in larger series is needed.